(3eaJGM GdYdhes - (3GdScGcj , SQGL GdOjf CHh jYbhH jhSa Hf CHj HcQ Hf eMeO Hf Ydj GdScGcj GdNhGQRej GdMfaj, GdScGcj,J (B626 (3g` s
(3ChdgG (B:s
(3HYO GdHSedI GdbSe GdKGdK ef GdcJGH GYde Cf Yde GdeYGfj gh JJHY NhGU JQGcjH GdcdGe aj GdGaGOI heG jJUd HgG ef s
(3BNQgG (B:s
(3heYQaI NhGUgG eeG jdRe UGMH GdeYGfj hGdHjGf hMjf dGYGOJg dRefG Gf dG TF ef LedJg s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B222 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B282s
Keywords: (3GdHdGZIs